The Harmony of Science and Practice in the Teaching of Kubrovia - Jabbarov Ikromjon Jumaniyazovich (International Journal on Integrated Education, 2024)
the emergence of Sufi teaching, its philosophical foundations, the upbringing of various sects, the orientation of Sufi ideas for the good, the classification of sciences in the Middle Ages, the importance of Sufi ideas in the spiritual maturity of man, the Sufi views of today's young generation. Scientific and philosophical analysis of the role, stages, ways and means of achieving truth in the spiritual, spiritual and ideological growth of a person in Kubrovi'es teaching, the state of Kubrovi'es teaching today throughout the world and in Uzbekistan